2020
DOI: 10.21203/rs.2.11846/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysing the preferences for family doctor contract services in rural China: a study using a discrete choice experiment

Abstract: Abstract Background: Preliminary evaluations have found that family doctor contract services (FDCSs) have significantly controlled medical expenses, better managed chronic diseases, and increased patient satisfaction and service compliance. In 2016, China proposed the establishment of a family doctor system to carry out contract services, but studies have found the uptake and utilization of these services to be limited. This study aimed to investi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…in Heilongjiang province suggested that there was a gap between actual and desired workplace characteristics, which had a negative influence on workers' job satisfaction [42]. The popular researches about family doctors focused on the effect and challenge of family doctor contract services [43][44][45][46][47][48], chronic disease management to contract with family [50] and assessment of Chinese family physicians' service competences [51]. Up to this point, these studies about job satisfaction and family doctors have been explored, however, these studies usually discussed other medical occupations or the effect of implementation family doctor policies, lacking of the overall occupational perception survey among family doctors at Community health centres.…”
Section: Introductionmentioning
confidence: 99%
“…in Heilongjiang province suggested that there was a gap between actual and desired workplace characteristics, which had a negative influence on workers' job satisfaction [42]. The popular researches about family doctors focused on the effect and challenge of family doctor contract services [43][44][45][46][47][48], chronic disease management to contract with family [50] and assessment of Chinese family physicians' service competences [51]. Up to this point, these studies about job satisfaction and family doctors have been explored, however, these studies usually discussed other medical occupations or the effect of implementation family doctor policies, lacking of the overall occupational perception survey among family doctors at Community health centres.…”
Section: Introductionmentioning
confidence: 99%
“…e focus of family doctor contracted services has shifted from quantity to service quality and satisfaction [24,25]. At the same time, family doctors' sense of identification with their profession has improved, especially for professional status, work value, and sense of achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Family doctor contract services are aimed to maintain the health of community residents, with general practitioners as the core, by providing comprehensive, continuous, and convenient basic medical and health services for residents, including preventive healthcare, diagnosis and treatment referrals for common and frequently occurring diseases, disease rehabilitation, chronic disease management, health management, etc. [1] In 2015, Shanghai launched a pilot program for "1+1+1" family doctor double contract service. In addition to residents signing contracts with one family doctor, they chose one district level hospital and one municipal hospital as their preferred higher-level hospitals for referral.…”
Section: Introductionmentioning
confidence: 99%